Exploring Zinc C295 as a Dual HIV-1 Integrase Inhibitor: From Strand Transfer to 3′-Processing Suppression - Sharif Karim Sayyed; Marzuqa Quraishi; D. S. Prabakaran; Balaji Chandrasekaran; Thiyagarajan Ramesh; Satish Kumar Rajasekharan; Chaitany Jayprakash Raorane; Tareeka Sonawane; Vinothkannan Ravichandran (Pharmaceuticals)
Background: The global AIDS pandemic highlights the urgent need for novel antiretroviral therapies (ART). In our previous work, Zinc C295 was identified as a potent HIV-1 integrase strand transfer (ST) inhibitor. This study explores its potential to also inhibit 3′-processing (3′P), thereby establishing its dual-targeting capability. Methods: The inhibitory activity of Zinc C295 against 3′P was evaluated using a modified in vitro assay adapted from our earlier ST inhibition studies. Molecular docking and molecular dynamics simulations were employed to analyse Zinc C295’s interactions with the 3′P allosteric site of HIV-1 integrase. Results: Zinc C295 demonstrated significant inhibition of HIV-1 integrase 3′P activity in in vitro assays (IC50 = 4.709 ± 0.97 µM). Computational analyses revealed key interactions of Zinc C295 within the enzyme’s allosteric site, providing insights into its dual inhibitory mechanism. Conclusions: Zinc C295’s dual inhibition of HIV-1 integrase ST and 3′P establishes it as a promising candidate for next-generation ART. Its dual-action mechanism may offer potential advantages in enhancing treatment efficacy and addressing drug resistance. Further studies are warranted to evaluate its therapeutic potential in clinical settings.